2018
DOI: 10.1158/0008-5472.can-17-3677
|View full text |Cite
|
Sign up to set email alerts
|

Heterochromatin Protein 1α Mediates Development and Aggressiveness of Neuroendocrine Prostate Cancer

Abstract: Neuroendocrine prostate cancer (NEPC) is a lethal subtype of prostate cancer arising mostly from adenocarcinoma via neuroendocrine transdifferentiation following androgen deprivation therapy. Mechanisms contributing to both NEPC development and its aggressiveness remain elusive. In light of the fact that hyperchromatic nuclei are a distinguishing histopathologic feature of NEPC, we utilized transcriptomic analyses of our patient-derived xenograft (PDX) models, multiple clinical cohorts, and genetically enginee… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 51 publications
(133 reference statements)
2
53
0
Order By: Relevance
“…59 NEPC loses the characteristics of the luminal epithelium, making its biological features different from those of ADENO. 60 The NEPC phenotype and molecular characteristics are associated with stronger invasiveness and metastasis, low or absent androgen receptor (AR) expression, RB loss combined with p53 dysfunction, and upregulated expression of neuroendocrine genes such as chromogranin A and neuron-specific enolase. 37,61,62 This transformation causes NEPC to no longer respond to typical AR pathway inhibition (ARPI).…”
Section: Discussionmentioning
confidence: 99%
“…59 NEPC loses the characteristics of the luminal epithelium, making its biological features different from those of ADENO. 60 The NEPC phenotype and molecular characteristics are associated with stronger invasiveness and metastasis, low or absent androgen receptor (AR) expression, RB loss combined with p53 dysfunction, and upregulated expression of neuroendocrine genes such as chromogranin A and neuron-specific enolase. 37,61,62 This transformation causes NEPC to no longer respond to typical AR pathway inhibition (ARPI).…”
Section: Discussionmentioning
confidence: 99%
“…11,17,59 Other studies also suggested that neuroendocrine transdifferentiation of PADCs be driven by variable genetic mechanisms such as overexpression of SRRM4, 60 hypoxia-mediated signaling, 43,61 PKC-lambda/iota reduction, 62 and elevated HP1a expression. 63 In addition, tumor-associated macrophages (TAMs) are an important component of tumor microenvironment. Recently Zarif et al 64 showed that TAM can reprogram tumor phenotype and play a major role in the emergence of a neuroendocrine phenotype in prostate cancers.…”
Section: Lineage Plasticity Driving Development Of Nepcmentioning
confidence: 99%
“…Ci et al 63 recently identified 36 heterochromatin-related genes by analysis of patient-derived xenograft, multiple patient cohorts, and genetically engineered mouse models. They showed that NEPCs have a distinctive heterochromatin gene signature compared with PADCs.…”
Section: Elevated Hp1a Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this protocol, we provide a simple and practical solution to overcome this technical hurdle. This method was employed in our recent study, providing in vitro evidence of the essential function of a gene named HP1α in maintaining NEPC aggressiveness (8).…”
Section: Introductionmentioning
confidence: 99%